Basics and Biomedical Applications of Dielectric Barrier Discharge (DBD) - Bibinov, Nikita; Rajasekaran, Priyadarshini; Wandke, Philipp Mertmann Dirk; Viöl, Wolfgang; Awakowicz, Peter (IntechOpen, 2011)
None